The Severity, Quality of Life, and Correlated Factors of Chronic Kidney Disease-associated Pruritus between Hemodialysis and Kidney Transplant Patients: A Cross-sectional Study - Melody Febriana Andardewi; Lili Legiawati; Danang Tri Wahyudi; Maruhum Bonar Hasiholan Marbun; Larisa Paramitha Wibawa (Interna Publishing, 2024)
Background: Chronic kidney disease-associated pruritus (CKD-aP) mainly occurs in hemodialysis (HD) patients and could persist in kidney transplant (KT) recipients. This study aims to compare the severity, correlation of various biochemical factors, and quality of life (QoL) concerning pruritus in CKD. Methods: A cross-sectional study was conducted on HD and KT recipients with chronic pruritus, where the 5-Dimensional (5-D) Itch Scale and Dermatology Life Quality Index (DLQI) were used to evaluate pruritus severity and QoL. Results: Among the 60 subjects, 76.7% of HD patients had moderate-to-severe pruritus, whereas in the KT group, 83.3% experienced mild pruritus (p < 0.001). The median DLQI score was 5 (3-6) and 3 (2-4), respectively (p < 0.001). There was a correlation between hs-CRP and the 5-D itch score in the HD group (r = 0.443; p < 0.05), whereas e-GFR was correlated with the 5-D itch score in the KT group (r = −0.424; p < 0.05). Conclusion: Moderate-to-severe pruritus was more common in HD patients. While pruritus in KT recipients had a mild effect on QoL, pruritus in the HD group had a mild-moderate impact on QoL. There was a correlation between hs-CRP and e-GFR and the severity of pruritus in HD and KT recipients, respectively.